2019
DOI: 10.3390/nu11030634
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Three Cooked Non-Cereal Starchy Foods on Postprandial Glycemic Responses and in Vitro Carbohydrate Digestion in Comparison with Whole Grains: A Randomized Trial

Abstract: Plant origin, processing, and domestic preparation may affect the postprandial glycemic response (PGR) of starchy foods. The objective of this study was to examine the possibility of integrating domestically cooked non-cereal starchy foods commonly consumed in Northeast Asia into glycemic management diet, and compare their glycemic characteristics with those of waxy and non-waxy whole grains and starchy beans. In a randomized crossover trial, ten healthy subjects consumed dried lily bulb (LB), lotus seed (LS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Previous studies show that the rate of carbohydrate digestion of starchy foods can be modified by the source, processing, and culinary preparation [ 16 ]. Compared to the reference sample, the EDA powder, after extrusion and milling, had a lower in vitro digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that the rate of carbohydrate digestion of starchy foods can be modified by the source, processing, and culinary preparation [ 16 ]. Compared to the reference sample, the EDA powder, after extrusion and milling, had a lower in vitro digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Adzuki bean polysaccharides possessed significant hypoglycemic activity and mitigated damage to pancreas tissues in STZ‐induced diabetic mice (Wu et al., 2019). Adzuki bean can maintain low glycemic index even after extended presoaking and prolonged cooking (Zhu et al., 2019). A controlled trial has also shown that extruded adzuki bean food can significantly inhibit inflammation in patients with T2DM (Liu et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported the glycemic index of cooked coix seed as 55.3 16 and 91 to 100, 17 which showed that its digestibility depends on the cooking method. 16,17 As described above, a comprehensive review of human studies indicates that coix seed may enhance the spontaneous regression of viral skin infections and may also reduce pruritus. Additionally, both effects could be exerted via alteration of the immune system.…”
Section: Discussionmentioning
confidence: 99%